The factors affecting switching behaviour from conventional bank into Islamic bank among government employess in Alor Setar / Nur Zafirah Mohammad Nasir - Mohammad Nasir, Nur Zafirah (2018)
The establishment of Islamic bank in 1983 has widen the eyes of banking industry consumer that the Islamic banking systems are able to compete and parallel with the conventional bank. Due to the establishment of Islamic bank, the account holder of conventional bank has put their interest to switch into Islamic bank. Switching behaviour is related with the attitude of the consumer that easily to move into other product or brand rather than loyal to the current product or brand. The switching behaviour are usually influenced by several factor that makes the customer trying to move into the others. According to Central Bank of Malaysia, on 2017 Islamic banking system deposits grew 26.6 per cent to RM436, 327.6 million comprising 26.6 per cent of the total deposits compare to conventional bank. Thus, the issue arises since the account holder of conventional bank slowly dropped. The researchers conduct the survey to determine the most influence factors that contribute the conventional bank consumer switch into Islamic bank. Hence, researcher can know how far the price factor, service quality, banking product offered, advertising and geographical location affect switching behaviour of conventional banking into Islamic bank. This study identifies the factors of Malaysian banking industry switching behaviour and determines relationship factors that contribute the consumer to switch the bank. Besides, this study evaluates the positive impact of price factor, service quality, banking product offered advertising and geographical location towards switching behaviour of conventional banking into Islamic bank.